ELEMEN STRUKTUR BANGUNAN MESJID â€œSAKA TUNGGALâ€ BAITUSSALAM DI CIKAKAK, WANGON, BANYUMAS - YOHANA NURSRUWENING; WITA WIDYANDINI (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2015)
ABSTRACTIn an effort to get close to the real problems of the building of this research istaking an object on Baitussalam mosque, located in the Cikakak Village,Wangon, Banyumas. This mosque has a uniqueness that is not owned by anothermosque, which is constructed by using only one pole (saka) of wood, which bearthe entire burden of the mosque, thatâ€™s way the mosque is known as the